ALAT PENGUSIR HAMA TIKUS SAWAH BERBASIS ARDUINO UNO DAN GELOMBANG ULTRASONIK - Iqbal, Mohammad; Rahayu, Andri Ulus (Teknik Elektro Universitas Siliwangi, 2022)
The development of electronic instrumentation technology is currently experiencing very rapid development, socializing and not a strange thing anymore. Technological advances are also very helpful in various sectors, one of which is the agricultural sector. Rice or in Latin, oryza sativa, is one of the most important cultivated plants in today's civilization. In the process of planting rice there are challenges that will be faced by farmers, one of which is the rat pest. The increase in cases of rat pests can cause severe damage to rice so that the number of farmers' rice harvests decreases. Attacks occur at night and attack mice in groups. The impact of this attack caused the rice stalks to break and the rice shoots to be eaten by rats. Various ways have been done by farmers to prevent mouse pests from attacking rice plants. In today's technological developments, these alternatives can be changed by utilizing technological sophistication, one of which is by designing an automation system tool using a microcontroller that can be adapted to certain needs so that it is expected to increase the effectiveness of the rice planting process starting from the processing time to the human resources themselves. In this case, researchers consisting of Naila, Aldi, Gemawan, and Susilawati designed an automation tool that can facilitate the work of farmers in protecting rice plants from rat pests. The mechanism for making this security sensor system is quite simple by using Arduino Uno as a microcontroller kit, and an ultrasonic sensor that will be installed as a mouse pest detection tool..